RETRACTED: Upaya Meningkatkan Kemampuan Fisik Motorik Kasar Anak melalui Kegiatan Melambungkan dan Menangkap dengan Berbagai Media Anak Usia Dini di TK Al- Fajar Pekanbaru - Melvi Lesmana Alim (LPPM Universitas Pahlawan Tuanku Tambusai, 2016)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal Obsesi to article entitled “Upaya Meningkatkan Kemampuan Fisik Motorik Kasar Anak melalui Kegiatan Melambungkan dan Menangkap dengan Berbagai Media Anak Usia Dini di TK Al- Fajar Pekanbaru” Vol 2, No 2, pp. 79-89, December 2016, This paper has been found to be in violation of the Jurnal PAUD Tambusai Publication principles and has been retracted. The article contained redundant material, the editor investigated and found that the paper published in Jurnal Obsesi, Vol. 1, No. 2, pp. 1-11, december 2015. The document and its content has been removed from Jurnal PAUD Tambusai, and reasonable effort should be made to remove all references to this article.